Brainstem Associated Somatosensory Evoked Potentials and Response to Vagus Nerve Stimulation: An Investigation of the Vagus Afferent Network - Suresh, Hrishikesh; Mithani, Karim; Brar, Karanbir; Yan, Han; Strantzas, Samuel; Vandenberk, Mike; Sharma, Roy; Yau, Ivanna; Go, Christina; Pang, Elizabeth; Kerr, Elizabeth; Ochi, Ayako; et al. (Frontiers in Neurology, 2022)
Despite decades of clinical usage, selection of patients with drug resistant epilepsy who are most likely to benefit from vagus nerve stimulation (VNS) remains a challenge. The mechanism of action of VNS is dependent upon afferent brainstem circuitry, which comprises a critical component of the Vagus Afferent Network (VagAN). To evaluate the association between brain stem afferent circuitry and seizure response, we retrospectively collected intraoperative data from somatosensory evoked potentials (SSEP) related to brainstem function in 7 children with drug resistant epilepsy who had failed epilepsy surgery and subsequently underwent VNS. Using multivariate linear regression, we demonstrate a robust negative association between SSEP amplitude (p < 0.01), and seizure reduction. There was no association between SSEP latency and seizure outcomes. Our findings provide novel insights into the mechanism of VNS and inform understanding of the importance of brainstem afferent circuitry within the VagAN for seizure responsiveness following VNS.